Seropositivity of COVID-19 Among Healthy Voluntary Blood Donors and Its Association with Blood Groups: A Reflection of Burden of Asymptomatic COVID-19 Cases in The District of South Gujarat - Kumar M, Kiran; Bhuva, Dimel; Patel, Snehal; Shah, Ankita; Kavishvar, Abhay (National Journal of Community Medicine, 2022)
Introduction: First case of COVID-19 in the district was reported on 19th March 2020, thereby increasing exponentially, presenting with various symptoms to having few or no symptoms, posing challenge to prevent disease transmission by being a significant source of infection. This study conducted to assess relationship between COVID-19 infection within blood groups and burden of reported cases in the district to seropositivity among donors. Methodology: This is a prospective observational study from second largest blood bank of south Gujarat, catering to a population of seven million, 4916 donors from the month of August 2020 to May 2021 participated in the study. Observations: Seropositivity was found to be 54.6%, with higher prevalence (68.63%) among female compared to male (54.45%), there was no statistical difference among age groups & RH groups, blood group AB was found to have highest seropositivity followed by A, B and O group. First time donors seropositivity was higher compared to frequent donors among the study participants. Seropositivity among donors was positively corelated with RTPCR Positivity rate reported in the district. Conclusions: Looking at similar trend of active surveillance and its correlation to blood bank positivity, we urge policy makers to strengthen hospital-based surveillance for real time insights.